PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KSP LOHJINAWE - Utami, Agustina Setyo; Waluyo, Handoyo Djoko (Jurnal Ilmu Administrasi Bisnis, 2017)
The problem found in this study is based on the development data of Lohjinawe Savings and Loan Cooperative (KSP) in 2013 to 2015, it indicates that many things do not reach the target, this is may be the implementation of organizational culture in Lohjinawe Savings and Loan Cooperative (KSP) is not going well. It indicates that the employees have not responsibility in their work that causes working result is not maximum. Lijan Poltak Sinambela, (2012: 3) states that employees performance is defined as the employee’s ability in doing a certain skill.The purpose of this study is to know the influence of organizational culture, motivation and disciplinary working to the employee performance. The type of this research is explanatory research. The population is all employees of Lohjinawe Savings and Loan Cooperative (KSP) with total of 54 employees. The data collection used in this research is questionnaire through validity and reliability test, interview and observation. The data analysis used is simple and multiple linear regression, correlation coefficient, coefficient of determination, significance test (t test an F test) with SPSS 20.0 version.The result shows that the correlation of organizational culture on employee performance is in the number of 0.453. The coefficient of determination (R2) of organizational culture to the employee performance is 20.6%. The correlation of motivation to the employee performance is low and it is in the number of 0.353. The coefficient of determination (R2) of motivation to the employee performance is 12.4%. The correlation of disciplinary working to the employee performance is in the number of 0,375. The coefficient of determination (R2) of working discipline to the employee performance is 14.0%. Simultaneously, organizational culture, motivation and working discipline give significant effect to the employee performance with F calculation (6.299) > F table (2,790) with significance value is 0.001 < 0.05. The conclusion of this study is the organizational culture, motivation and disciplinary working give positive effect to the employee performance in the Lohjinawe Savings and Loan Cooperative (KSP).The suggestion to improve employee performance is to maintain the business continuity, the administrator of Lohjinawe (KSP) must have many strategies to increase the productivity by considering the factor of human resources working in that place. It is done in order to improve motivation and disciplinary working of work by making cultures to give positive value to the employees.